Single‐cell landscape of the intrahepatic ecosystem in alcohol‐related liver disease - Xiaofang Zhao; Senyan Wang; Qi Liu; Wenjuan Wei; Xiaoyan Sun; Hao Song; Jing Xu; Shuijun Zhang; Hongyang Wang; Jing Fu (Clinical and Translational Medicine)
Abstract Alcohol‐related liver disease (ALD) is a common chronic liver disease caused by long‐term excessive alcohol consumption and responsible for more than half of all liver‐related deaths worldwide. The molecular mechanisms associated with ALD were not fully understood. In this study, we performed single‐cell RNA sequencing on liver tissues obtained from ALD patients and healthy liver donors. We identified an ALB+KRT7+ epithelial population that expressed both hepatocyte and biliary markers significantly expanded in ALD livers. The ALB+KRT7+ epithelial cells were demonstrated to have stem cell properties and malignant transformation potentials. Moreover, ALB+KRT7+ epithelium‐derived ALD organoids promote the tumour growth by activating Wnt/β‐catenin signalling of liver cancer cells. Most importantly, blocking the Wnt protein secretion or knockdown the Wnt receptor suppressed the tumour promoting effect of ALD organoids. Our study provides important insights that Wnt signalling can be targeted in patients with advanced alcohol‐related cirrhosis to prevent malignant transformation. In addition, our results also uncovered the important alterations of nonparenchymal cells, especially macrophages and T/NK populations that responsible for active inflammation responses in alcohol‐related hepatitis and immunosuppressive microenvironment in advanced cirrhosis livers, which likely facilitated the malignant progression of ALD. Key points This study provides single‐cell landscape of human liver samples across different ALD stages. The ALB+ KRT7+ epithelium were enriched in ALD patients, and the function of this epithelial population varied significantly across ALD stages. ALB+KRT7+ epithelium from advanced alcohol‐related cirrhosis had malignant transformation potential and tumour promotion activity. The comprehensive changes of parenchymal and nonparenchymal cells in the ALD livers lay a hidden danger for the further malignant progression.